Bandgap tailoring and optical response of InAlAs/InGaAs/GaAsSb double quantum well heterostructures: the impact of uniaxial strain and well width variations. Issue 21 (15th December 2022) - Riyaj, Md.; Rathi, Amit; Singh, A. K.; Pushpalata,; Alvi, P. A.
ABSTRACT: In this research work, a theoretical approach has been adopted to study GaAs-based InAlAs/InGaAs/GaAsSb type-II heterostructures. The 6 × 6 k·p Hamiltonian matrix with self-consistent calculations has been carried out to calculate the wavefunctions, localization of the charge carriers (probability density of charge carriers) and their dispersed energy states (Discrete energy level) under variable quantum well width and external strain of the double quantum well heterostructure. Bulk band structures of InAlAs/GaA for different aluminium compositions have been reported. The quantum well size and external strain effect on optical gain have also been explored. Computational analysis showed the generated light has a 1.93 μm NIR lasing wavelength. At 12 GPa, optical gain reaches 7450 cm −1 and wavelength 1.93 μm. Peak gain is 5931 cm −1 for 2 nm well width. The developed type-II structure can be employed in a semiconductor laser diode operating in the NIR range as per the observed results.